2020
DOI: 10.4103/ajns.ajns_56_19
|View full text |Cite
|
Sign up to set email alerts
|

The satisfactory surgical outcome of posterior fossa brain tumors in children at civil hospital, karachi

Abstract: Introduction: Posterior fossa brain tumor is the most devastating forms of human illness, primarily because of the limited space within the posterior fossa, the potential involvement of vital brain stem nuclei, and the mass effect causes obstructive hydrocephalus. Posterior fossa tumors are more common in children than adults. The Objective of the Study: To find out the satisfactory surgical outcome of posterior fossa brain tumors in children at Civil hospital, Karachi. Materials and Methods and Duration of St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…This contrasts with a similar study by Jahanzaibkakar et al, which found a male-dominated population. 10 In our case study, the most prevalent clinical manifestation was headache and vomiting, which has also been documented in other case studies. Emara et al reported 90.9 percent of cases presenting with headache in their case series, which is very comparable to our results (90 percent)as mentioned in Table 1.…”
Section: Discussionsupporting
confidence: 85%
“…This contrasts with a similar study by Jahanzaibkakar et al, which found a male-dominated population. 10 In our case study, the most prevalent clinical manifestation was headache and vomiting, which has also been documented in other case studies. Emara et al reported 90.9 percent of cases presenting with headache in their case series, which is very comparable to our results (90 percent)as mentioned in Table 1.…”
Section: Discussionsupporting
confidence: 85%
“…More boys than girls are affected depending on tumor type and patient age. 8 Among all 60 patients most were(60%) male, so PFSOL in pediatric age group in Bangladesh is mainly male predominant which correlated with international data.…”
Section: Discussionsupporting
confidence: 69%
“…It was discussed that patients with papilledema, hemiparesis, and meningismus have comparatively low successive results in surgery with p value 0.011, 0.005 and 0.043, respectively. 14 On a national level, an American study included 17,610 patients; the male-to-female ratio was 1:3.5. IONM monitoring was necessarily used in 63.9% of cases.…”
Section: Discussionmentioning
confidence: 99%